1993
DOI: 10.1136/vr.132.2.35
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of abamectin against nematodes in cattle

Abstract: Eight controlled trials were conducted, using 96 cattle of European breeds, to evaluate the efficacy of abamectin against natural and artificially acquired infections of adult and fourth-stage larvae of all the economically important gastrointestinal nematodes and lungworms in Germany and the United Kingdom. Half the animals were treated on one occasion with abamectin at a dose of 200 micrograms/kg bodyweight given subcutaneously while the other half remained untreated. Worms were counted 14 or 21 days after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…For routine purposes, infective Cooperia species larvae cannot be identified to a species level and therefore the exact composition of the mixture of Cooperia larvae was not known. The composition of the burden of Cooperia species observed in both trials was similar to that observed after the use of the same isolates in previous studies (Heinze‐Mutz and others 1993, Pitt and others 1996, B. N. Kunkle, unpublished observations). The infection rates varied between the species.…”
Section: Resultssupporting
confidence: 86%
“…For routine purposes, infective Cooperia species larvae cannot be identified to a species level and therefore the exact composition of the mixture of Cooperia larvae was not known. The composition of the burden of Cooperia species observed in both trials was similar to that observed after the use of the same isolates in previous studies (Heinze‐Mutz and others 1993, Pitt and others 1996, B. N. Kunkle, unpublished observations). The infection rates varied between the species.…”
Section: Resultssupporting
confidence: 86%
“…Sua eficácia já foi demonstrada para o controle de ectoparasitos e nematoides de bovinos e sua eficácia é superior a 90% durante em média 28 dias (Abridi et al, 1992;Cruz et al, 1993;Heinze-Mutz et al, 1993a, 1993bGuglielmone et al, 1999).…”
Section: Discussionunclassified